A pyoverdine-based iron biochelate from bacterial secretions as an effective fertilizer under alkaline conditions - Lozano-González, José María; Lucena, Juan José; López-Rayo, Sandra (Frontiers in Plant Science, 2025)
IntroductionIron (Fe) deficiency in crops grown on calcareous soils seriously limits their productivity. The most common practice to address this issue is the application of Fe-chelates. However, more environmentally friendly methods are now being adopted. This study evaluated a pyoverdine-based siderophore extract from Pseudomonas RMC4 (Pvd) as an Fe biofertilizer.MethodsStability batch tests and plant assays were conducted, including ferric chelate reductase (FCR) activity, ⁵⁷Fe-labeled uptake, phytotoxicity, and a hydroponic test with cucumber plants at two Fe levels (5 and 10 µM).Results and discussionThe Pvd/Fe³⁺ biofertilizer showed high stability at alkaline pH and resistance to Ca²⁺ interference. Although only a limited reduction of Pvd/Fe³⁺ by FCR was observed, Fe showed efficient translocation to shoots. Pvd/Fe³⁺ improved root morphology and biomass, and decreased reactive oxygen species, demonstrating biostimulant effects. At 10 µM, Pvd/Fe³⁺ provided Fe supply efficiency comparable to commercial HBED/Fe³⁺, and improved Fe/Mn ratio. These findings support the potential of Pvd/Fe³⁺-based formulations as dual-function biofertilizers and biostimulants.